2002
DOI: 10.1002/hbm.10052
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared spectroscopy can detect brain activity during a color–word matching Stroop task in an event‐related design

Abstract: Brain activity can be monitored non-invasively by near-infrared spectroscopy (NIRS), which has several advantages in comparison with other imaging methods, such as flexibility, portability, low cost and biochemical specificity. Moreover, patients and children can be repetitively examined. Therefore, the objective of the study was to test the feasibility of NIRS for the event-related approach in functional brain activation studies with cognitive paradigms. Thus, changes in the concentration of oxy-, deoxy-, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
147
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(165 citation statements)
references
References 27 publications
16
147
2
Order By: Relevance
“…It has been pointed out that facilitation was not a necessary concomitant of interference and it played a much lesser role than interference [12]. It was asserted that the missing facilitation was due to trying to speed up an already rapid response [12], [14]. Additionally, as pointed out by an anonymous reviewer, the slower response to congruent trials may be related with the observation that the subjects try to judge whether the trial is congruent or incongruent, which puts an extra cognitive load with respect to neutral trials.…”
Section: A Behavioral Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been pointed out that facilitation was not a necessary concomitant of interference and it played a much lesser role than interference [12]. It was asserted that the missing facilitation was due to trying to speed up an already rapid response [12], [14]. Additionally, as pointed out by an anonymous reviewer, the slower response to congruent trials may be related with the observation that the subjects try to judge whether the trial is congruent or incongruent, which puts an extra cognitive load with respect to neutral trials.…”
Section: A Behavioral Resultsmentioning
confidence: 99%
“…Schroeter et al [14] had investigated the same type of Stroop task with fNIRS on healthy subjects. They found that the hemodynamic response was stronger for incongruent compared to neutral and congruent trials in the lateral prefrontal cortex, bilaterally both for oxy-Hb and deoxyHb (and total Hb, which is their sum).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are studies using cognitive stimuli that report "variable results"; this does not further our understanding of the NIRS methodology, neither proving the insufficiency of the method nor demonstrating a "variable" underlying physiologic process. Interestingly, one of the most solid cognitive studies, with the largest number of subjects and a statistically sound approach in a single trial design, was done by successive sampling with a 2-channel monitor (Schroeter et al, 2002). This may stress the fact that, besides the quality of the monitor used, study design and a sound statistical approach to the data obtained are equally important.…”
Section: Review Of the Studiesmentioning
confidence: 99%
“…To include that period, we chose a long intertrial interval of 60 s (Mildner et al, 2001). An event-related approach was employed to detect the hemodynamic response to a single trial (Burock et al, 1998;Schroeter et al, 2002Schroeter et al, , 2004c. Measurements were performed simultaneously with fMRI and fNIRS.…”
Section: Introductionmentioning
confidence: 99%